PERSEPSI SISWA TENTANG PENGGUNAAN ICE BREAKING DALAM PEMBELAJARAN BAHASA INGGRIS DI SD ALAM MUARA BUNGO - Febriani Nuryanti; Winda Trisnawati; Renda Lestari (Universitas Muhammadiyah Muara Bungo, 2025)
This research tittle is Students' Perceptions of Using Ice Breaking in English Learning at At Sd Alam Muara Bungo. English learning in elementary schools often faces challenges in maintaining student concentration and motivation. One strategy used is icebreaking, an activity to break the ice, increase engagement, and create a pleasant learning atmosphere. This study aims to describe the perceptions of fourth-grade students at Muara Bungo Natural Elementary School regarding the use of icebreaking in English learning. The research method used is descriptive qualitative with fourth-grade students as subjects. Data were obtained through semi-structured interviews, with interview protocol based on Bandura's social learning theory. Data analysis was conducted thematically using NVivo 12. The results showed that most students had positive perceptions, considering icebreaking to be calming, increase enthusiasm, focus, and self-confidence. However, a small number of students expressed negative perceptions, such as boredom due to the lack of variety and discomfort in participating. These findings emphasize the importance of icebreaking variations tailored to students' needs for optimal benefits.